2007
DOI: 10.1111/j.1572-0241.2007.01095.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Prognostic Determinants of Patients with Bacteremic Cholecystitis or Cholangitis

Abstract: Though the mortality rate in patients with bacteremic BTI is substantial, survival is better than in those with bacteremia from other sources. The main prognostic factors identified in this study may help clinicians recognize patients at high risk for early mortality so that they can give prompt, appropriate treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
62
4
8

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 25 publications
7
62
4
8
Order By: Relevance
“…In the present study, CRP levels were significantly higher in CBDdil(-) patients than in CBDdil(+) patients. Previous studies have demonstrated that increased levels of CRP, WBCs and T-Bil are associated with severe acute cholangitis and poor patient prognosis (22,23). In the current study, WBC count and T-Bil levels did not differ significantly between the CBDdil(-) and CBDdil(+) groups, suggesting that the severity of acute cholangitis was similar between the groups.…”
Section: Discussionsupporting
confidence: 53%
“…In the present study, CRP levels were significantly higher in CBDdil(-) patients than in CBDdil(+) patients. Previous studies have demonstrated that increased levels of CRP, WBCs and T-Bil are associated with severe acute cholangitis and poor patient prognosis (22,23). In the current study, WBC count and T-Bil levels did not differ significantly between the CBDdil(-) and CBDdil(+) groups, suggesting that the severity of acute cholangitis was similar between the groups.…”
Section: Discussionsupporting
confidence: 53%
“…A pesar de que inicialmente parece obvio que los pacientes con cáncer tendrán una sobrevida más corta, ello podría no ocurrir cuando el grupo comparador tiene, en promedio, una edad dos décadas superior como en este caso. Otro aspecto relevante es que la patología neoplásica maligna resultó ser una causa frecuente en el desarrollo de colangitis bacteriémica llegando a explicar un tercio de los casos de esta serie, un hallazgo importante por la baja sobrevida ya comentada y por su estrecha asociación con un fracaso en el tratamiento de colangitis, con o sin bacteriemia 2,3 . Otras publicaciones describen hasta 50% de fracaso del tratamiento de la bacteriemia en los casos asociados a neoplasia maligna.…”
Section: Discussionunclassified
“…Akut kolesistit, safra kesesinin başlangıçta inflamatuar bir hastalığı-dır ve büyük oranda safra taşlarına bağlı olarak gelişir (13,21) . Safra taşı prevalansı ülkeler arasında farklılıklar göstermektedir.…”
Section: Discussionunclassified
“…Çoğu asemptomatik olmakla beraber olguların ortalama % 20'sinde infeksiyon komplikasyonları gelişebil-mektedir. İlerlemiş tedavilere rağmen bakteriyel biliyer sistem infeksiyonlarında mortalite (% 10-20) önemini korumaktadır (13) . Uzun yıllardır, bakteriler tarafından salgı-lanan beta-glukronidazın, biluribin glukronidi serbest biluribin ve glukronik aside parçalayan enzimatik hidrolizindeki kritik faktör olduğu düşünülmektedir.…”
Section: Discussionunclassified
See 1 more Smart Citation